2018
DOI: 10.1159/000487332
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Neurological Decline with Deep Bilateral Imaging Changes: A Protean Presentation of Dural Arteriovenous Fistulae

Abstract: Intracranial dural arteriovenous fistulae (DAVF) within the deep cerebral vasculature are diagnostically challenging because of their variable clinical presentation and typical bilateral neuroimaging findings mimicking inflammatory, infectious, and metabolic processes. Increasingly, reports have emerged highlighting the diagnostic and treatment challenges of these lesions and their associated high morbidity and rapid clinical deterioration when untreated. We describe here a case series of 4 patients with deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…2,17 Several imaging features are described in dementia due to DAVF such as diffuse white matter hyperintensity secondary to venous congestion, medullary vein dilatation, thalamic and brainstem edema (in thalamic dementia), and hypoperfusion of frontal and temporal lobes on single-photon emission computerized tomography (SPECT) studies. 6,12,18,19 Most of these imaging features could be correlated to cognitive decline that has already been manifested. There are no imaging predictors to cognitive decline in DAVF, although cortical venous reflux has been mentioned as one of the risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,17 Several imaging features are described in dementia due to DAVF such as diffuse white matter hyperintensity secondary to venous congestion, medullary vein dilatation, thalamic and brainstem edema (in thalamic dementia), and hypoperfusion of frontal and temporal lobes on single-photon emission computerized tomography (SPECT) studies. 6,12,18,19 Most of these imaging features could be correlated to cognitive decline that has already been manifested. There are no imaging predictors to cognitive decline in DAVF, although cortical venous reflux has been mentioned as one of the risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 There is limited evidence to say that imaging parameters predict the development, or progression of cognitive decline in DAVF, or its potential reversibility after treatment. 5,11,12 Resting-state functional magnetic resonance imaging (RS-fMRI) is a promising imaging research tool that reveals the functional connectivity (FC) changes and interaction among resting-state networks (RSNs) in cognitive disturbances and dementia. 13,14 FC changes in RSNs may be related to the symptom manifestation and may uncover the pathophysiological mechanisms in early changes or disease severity in many neurodegenerative disorders.…”
mentioning
confidence: 99%
“…[13,14] We reviewed the literature of patients with thalamic dementia caused by venous hypertension of bilateral thalami from cranial DAVFs and found 28 cases, including our present case, with 30 fistulas due to bilateral lesions in two cases [Table 1]. [8,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The collected data in this review included demographic data (i.e., gender and age of patient), location and arterial supply of the fistulas, symptoms and signs of the patients, angiographic occlusion of the straight sinus, presence of intracerebral hemorrhage, treatment of the fistulas, and neurological outcome after treatment. From the literature review, there were 25 men (89.3%) and 3 women (10.7%) with median age of 59.5 years, ranging from 43 to 77 years.…”
Section: Discussionmentioning
confidence: 99%
“…[25,27,29] Most patients harboring tentorial DAVFs including our case had angiographic occlusion of the straight sinus. [8,[14][15][16]18,21,22,24,25,27,29,30,32] Interestingly, Iwasawa et al [28] reported a patient with DAVF at transverse-sigmoid sinus without thrombosed straight sinus and speculated that an anatomical variation, i.e., noncommunication between the right and left transverse sinuses, may play a major role in producing thalamic dementia by increasing drainage into the deep venous structure. Tanaka et al [17] reported a patient with tentorial DAVF associated with occlusion of bilateral transverse sinuses compromising hemodynamics into bilateral thalami.…”
Section: Discussionmentioning
confidence: 99%
“…DAVFs located at the tentorial edge, at the torcular erophili or at the transverse-sigmoid junction, directly draining into the deep venous system and finally involving the vein of Galen and internal cerebral veins, can manifest themselves with symptoms of thalamic dementia which is a less frequent presentation modality with a few dozen cases reported in literature [7][8][9] . The mode of presentation is usually rapidly progressive (from weeks to a few In the appropriate clinical setting, DAVF should always be considered in the differential diagnosis of bilateral thalamic hyperintensities and the suspicion for vascular etiology should increase if bleeding or microbleeds are found in the same or adjacent brain regions.…”
Section: A C C E P T E Dmentioning
confidence: 99%